Food Consumption Patterns of Male and Female Undergraduate Students in Indonesia During New Normal Implementation of Pandemic Covid-19 Era - Kristiandi, Kiki; Yunianto, Andi Eka; Darawati, Made; Doloksaribu, Tetty Herta; Anggraeni, Ike; Pasambuna, Muksin; Akbarini, Oon Fatonah (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aimed to analyze the description of Indonesian undergraduate students’ food consumption patterns during the COVID-19 period. METHODS: The design used was cross-sectional with random sampling technique. The correlation test was Chi-Square and analyzed using univariate. The respondents involved were 17–24 years old with 5924 persons; active undergraduate students. Questionnaires were distributed using Google form. RESULTS: The results indicated a relationship between gender and major, education level, social status, and funds source (p = 0.000). However, sex and residence did not correlate (p = 0.16). The same was revealed between gender with consumption patterns, carbohydrates, animal protein, vegetable protein, vegetables, fruit, snacks, water, and supplements. CONCLUSION: Overall, during the new normal period of pandemic COVID-19 era, student food consumption patterns could be categorized as healthier lifestyle changes. Thus, the undergraduate students are suggested to maintain a diverse and balanced diet to boost their immunity optimally.